2021
DOI: 10.1021/acsengineeringau.1c00012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Growth Kinetics of Methane Hydrate in Stirred Tank Batch Reactors

Abstract: Hydrate formation could be looked upon as multicomponent and multiphase reaction which is heavily dependent on mass transfer and heat transfer limitations even under favorable thermodynamic conditions. Gas uptake measurement is one of the easiest ways to understand the kinetics of hydrate growth. In a typical gas uptake measurement, one could easily observe three phases of hydrate formation: in phase-I, hydrate forming gas dissolves in the liquid phase which leads to hydrate nucleation; in phase-II, fast hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Moreover, the CP layer is expected to adversely affect hydrate formation. A number of studies , reported that the formation of hydrate was prolonged as a result of the aforementioned hindering effect. A longer induction time is undesirable in a practical water desalination process using gas hydrate formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the CP layer is expected to adversely affect hydrate formation. A number of studies , reported that the formation of hydrate was prolonged as a result of the aforementioned hindering effect. A longer induction time is undesirable in a practical water desalination process using gas hydrate formation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, “stirring mode” is the frequently used terminology in the literature indicating the mechanical stirring speed/rate. In hydrate research, the effect of stirring speed on the hydrate formation process has been reported in publications where the range of tested stirring speeds was between 200 and 1000 rpm, and it has been established that no improvements in hydrate formation are observed using speeds higher than 600 rpm. ,, In addition, most studies on methane hydrate formation kinetics have used higher driving forces, such as pressures of about 60 to 80 bar, and a minimum stirring speed of about 300–500 rpm. Therefore, in this work, we considered low stirring mode as below 200 rpm.…”
Section: Introductionmentioning
confidence: 99%
“…Gas hydrate formation typically consisted of three phases: phase I, which involved dissolution of gas in liquid; phase II, wherein rapid hydrate formation/growth was observed; and phase III, wherein a slow hydrate growth rate was evident due to the pressure drop in the reactor and reduced mass transfer. Gootam et al 185 developed a model to predict the hydrate growth during phase II events in a batch/semi-batch reactor based on the earlier model that captured intrinsic kinetics of hydrate growth in a semi-batch reactor. The model predicted the rapid hydrate growth in phase II through a moments-based approach in solving the population balance model.…”
Section: Modeling and Simulation Studies On Gasmentioning
confidence: 99%
“…Thus, for example, Linga et al found that fixed bed silica sand performed better than the stirred reactor 18 . Recent studies such as Gootam et al showed that a top-mounted stirrer can improve the rate constant due to more efficient mixing 19 . However, scale-up studies that involved both heat and mass transfer analysis showed that the stirred-reactor configuration is not favorable for any significant economic scale-up 20 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Recent studies such as that of Gootam et al showed that a topmounted stirrer can improve the rate constant due to more efficient mixing. 19 However, scale-up studies that involved both heat and mass transfer analysis showed that the stirred-reactor configuration is not favorable for any significant economical scale-up. 20 This conclusion can be explained by the lower hydrate mass in water (≤5 wt %), agitation energy cost as the slurry thickens, and postprocessing cost of filtration and packing.…”
Section: ■ Introductionmentioning
confidence: 99%